2004
DOI: 10.1007/s00464-003-9243-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic esophagectomy in the palliative treatment of advanced esophageal cancer after radiochemotherapy

Abstract: The laparoscopic approach seems to be effective for the palliative treatment of advanced esophageal cancer. Further trials will be necessary to evaluate the advantages of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, very few series have reported a longer follow-up period than ours: Del Genio et al, 26 at a mean follow-up of 20.2 months (range: 10 to 40 mo), reported an incidence of mortality of 31.6%; Avital et al 28 recorded an average follow-up of 30 months (range: 12 to 48 mo), an overall survival of 61%, and a disease-free survival of 39%; Kent and coworkers, 45 in a reanalysis of the dataset of the 222 patients who underwent minimally invasive esophagectomy, demonstrated 1-year, 3-year, and 5-year survivals of 69%, 45%, and 36%, respectively; Leibman et al 32 recorded a median follow-up of 32 months (range: 2 to 55 mo), with 60% of the patients developing recurrence of cancer after the surgery, the median time to recurrence being 11 months, and the overall median survival, 32 months (range: 1 to 46 mo); more recently, Smithers et al 46 recorded a inhospital operative mortality rate of 2.6% for the open approach, 2.2% for the thoracoscopic-assisted group, no deaths in the total minimally invasive esophagectomy (MIE) group, and no difference in the time to recurrence between the 3 groups for patients with invasive cancer; this study showed the overall survival to be 24%, that of the total MIE group to be 25%, and the 3-year and 5-year survival rates to be 30% and 16%, respectively, for the overall group, and 33% and 22%, respectively, for the ng total MIE group.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…To the best of our knowledge, very few series have reported a longer follow-up period than ours: Del Genio et al, 26 at a mean follow-up of 20.2 months (range: 10 to 40 mo), reported an incidence of mortality of 31.6%; Avital et al 28 recorded an average follow-up of 30 months (range: 12 to 48 mo), an overall survival of 61%, and a disease-free survival of 39%; Kent and coworkers, 45 in a reanalysis of the dataset of the 222 patients who underwent minimally invasive esophagectomy, demonstrated 1-year, 3-year, and 5-year survivals of 69%, 45%, and 36%, respectively; Leibman et al 32 recorded a median follow-up of 32 months (range: 2 to 55 mo), with 60% of the patients developing recurrence of cancer after the surgery, the median time to recurrence being 11 months, and the overall median survival, 32 months (range: 1 to 46 mo); more recently, Smithers et al 46 recorded a inhospital operative mortality rate of 2.6% for the open approach, 2.2% for the thoracoscopic-assisted group, no deaths in the total minimally invasive esophagectomy (MIE) group, and no difference in the time to recurrence between the 3 groups for patients with invasive cancer; this study showed the overall survival to be 24%, that of the total MIE group to be 25%, and the 3-year and 5-year survival rates to be 30% and 16%, respectively, for the overall group, and 33% and 22%, respectively, for the ng total MIE group.…”
Section: Discussionmentioning
confidence: 61%
“…Subsequently, several authors have demonstrated the feasibility and safety of the laparoscopic approach to esophageal cancer. [26][27][28][29][30][31][32] In contrast, no advantages were recorded for the application of thoracoscopic techniques. 16,24,33,34 Although laparoscopic surgery for benign esophageal disease has met with widespread acceptance, minimally invasive esophagectomy did not meet with the same approval, on the ground of malignant disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking across studies that used minimally invasive esophageal mobilization for esophagectomy, average duration of thoracoscopy part varied between 104–226 min, and average hospital stay was between 8 and 26 days 9,12–21 . Thirty‐day mortality rate varied between 0% and 13.6%.…”
Section: Discussionmentioning
confidence: 99%